IPTEKS SISTEM DAN PROSEDUR PENGELUARAN KAS PADA UPTD BALAI PENDIDIKAN DAN PELATIHAN KOPERASI DAN UKM DAERAH PROVINSI SULAWESI UTARA - Lasupu, Erika Zhavira; Wangkar, Anneke (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Cash expenditure is the most important component in implementing development programs that will be carried out by the government. In cash expenditures the government has a system and procedures for managing and controlling financial expenditures. North Sulawesi Cooperative and SME Education and Training Center as regional technical implementers involved in cooperatives and SME education and training in North Sulawesi Province, of course the expenditure and receipt of cash must be in accordance with procedures stipulated by the government in the regulations per invitation law. Based on research conducted at the UPTD of the North Sulawesi Province Cooperative and SME Education and Training Center, the UPTD of the North Sulawesi Province Cooperative and SME Education and Training Center has effectively referred to the Minister of Home Affairs regulation Number. 59 of 2007. However, in its implementation there are still shortcomings, namely in the process of submitting SPP (UP-GU-TU-LS) without authorization of PPK-SKPD and some processes have a lack of attachments to complete submissions. The suggestions that can be given by researchers in implementing cash disbursement procedures at the UPTD of North Sulawesi Province Cooperative and SME Education and Training Centers must be in accordance with the applicable provisions but must be able to adjust if there is a change in regulation as a reference in regional financial management.Keywords: Analysis, Application, System, Procedure, Expenditure, Cash